Lilliputian hardware platform for scientific applications - Iyer, Neelima; Khatavkar, Rupali; Joshi, Bhagyashree; Upadhye, V. (International Journal of Software Engineering and Knowledge Engineering, 2005)
Microcontroller plays an important role in gearing up scientific applications for measurements, data acquisition and controls. With the advent of technology in microcontrollers, a new era in the form of microconverter is available at the user's doorstep. Benefited by the excellent features of Analog Devices' microconverter chip ADuC 842, an attempt has been made to develop a Lilliputian platform for scientific applications at National Chemical Laboratory (NCL), Pune. A real time system has been developed for measuring surface tension exerted by Langmuir films formed at air water interface. The films are compressed by smooth and precision barrier mechanism through DC motor in a controlled manner. (IC)-C-2 compatible EEPROM is provided on board for data storage and it can be communicated to a PC through RS232 link for further analysis. The other features provided are, In-circuit programming for firmware updating, keyboard functioning for special routine executions, (IC)-C-2 compatible RTC and battery backup. The software has been completely developed using assembly language programming. Intelligent Lilliputian platform designed using ADuC 842 chip and graphic LCD for real time plotting of surface pressure area isotherm of Langmuir films has been developed and tested successfully at NCL.
1st International Embedded and Hybrid Systems Conference, Singapore, SINGAPORE, MAY 11-13, 2005
Keywords: Langmuir films; microconverter